Pedobacter ghigonii sp. nov., Isolated from the Microbiota of the Planarian Schmidtea mediterranea - Luis Johnson Kangale; Didier Raoult; Fournier Pierre-Edouard (Microbiology Research, 2021)
The planarian S. mediterranea is a platyhelminth with worldwide distribution that can regenerate any part of its body after amputation and has the capacity to eliminate a large spectrum of human bacterial pathogens. Surprisingly, the microbiota of S. mediterranea remains poorly investigated. Using the culturomics strategy to study the bacterial component of planarians, we isolated a new bacterial strain, Marseille-Q2390, which we characterized with the taxono-genomic approach that associates phenotypic assays and genome sequencing and analysis. Strain Marseille-Q2390 exhibited a 16S rRNA sequence similarity of 99.36% with Pedobacter kyungheensis strain THG-T17T, the closest phylogenetic neighbor. It is a white-pigmented, Gram-negative, and rod-shaped bacterium. It grows in aerobic conditions and belongs to the family Sphingobacteriaceae. The genome of strain Marseille-Q2390 is 5,919,359 bp-long, with a G + C content of 40.3%. By comparing its genome with other closely related strains, the highest Orthologous Average Nucleotide Identity (Ortho-ANI) and digital DNA-DNA hybridization (dDDH) values were 85.71% and 30.50%, respectively, which were found with Pedobacter soli strain 15-51T. We conclude that strain Marseille-Q2390T is sufficiently different from other nearby species to be classified within a new species for which we propose the name Pedobacter ghigonii sp. nov.